Enhancing Handball Shooting Skills: The Effectiveness of a Website-Based Training Model for Youth Athletes - Arif, Muhamad; Sukriadi, Slamet; Dwi, Dicky Reva Apriana Sanga; Ramadan, Gilang (Physical Education Theory and Methodology, 2025)
Objectives. This study aimed to explore the development and supportive role of a website-based training model designed to complement coach-led instruction and improve handball shooting skills in athletes aged 15–17. Traditional training methods have limitations in engagement and consistency, which the web-based model seeks to mitigate by enhancing athlete–coach interaction and accessibility. Materials and Methods. The study employed a Research and Development (R&D) design, following the Borg and Gall model, with a pre-test and post-test design. The experimental group (n = 20) used the website-based model under coach supervision, while the control group (n = 20) followed conventional training methods. Data was collected through shooting accuracy tests, surveys, interviews, and observations. Results. The results revealed that the experimental group demonstrated a significantly greater improvement in shooting accuracy, with an N-Gain of 63.90% (95% CI [58.7, 69.1]; p < .001), compared to the control group’s N-Gain of 24.62% (95% CI [20.3, 29.0]). The website-based model was found to be supportive and effective in standardizing improvements and providing flexible, coach-assisted interactive training. However, challenges such as athlete resistance to new methods and technology access issues were identified. Conclusions. The study highlights the potential of digital tools in sports training, emphasizing the need for blended implementation with traditional coaching and continued development to address technical and accessibility challenges. Further research should be conducted to investigate the long-term integration, scalability, and coach-mediated implementation of this training model across various sports and age groups.